Effect of Static and Dynamic Stretching during Warm-up on Balance in Physical Education Female Students - Mohammadtaghi Amiri-Khorasani; Mansooreh Mogharabi Manzari (Vesnu Publications, 2014)
Introduction: One of the main sections of warm up is stretching which the importance of them is static and dynamic stretching. The purpose of this study was to examine the effects of static and dynamic stretching within a pre-exercise warm-up on the static and dynamic in soccer players. Materials and Methods: Eighteen physical education female students (height: 159.68 ± 5.94 cm; mass: 60.21 ± 5.93 kg; age: 22.00 ± 0.63 years (Mean ± SD)) were participated voluntarily. Before and after different warm-up protocols consisting of static stretching (SS), dynamic stretching (DS), and no stretching (NS), to measure static and dynamic balance were used the stork test and the star excursion balance test, respectively. Statistical analysis was conducted ANOVA Repeat Measure and Tukey's testes. Results: There was a significant increase in static balance after DS (6.34 ± 3.14 s) vs. SS (4.40 ± 2.47 s) (p = 0.03). In addition, there was a significant increase in dynamic balance after DS (72.03 ± 3.76) vs. SS (69.58 ± 5.35) (p = 0.01). One the other hand, there are no significant differences in static and dynamic balance after NS vs. DS and SS. Conclusion: Researchers concluded that dynamic stretching cause to increase the static and dynamic balance performance. Therefore, they should update their body with this type of stretching.   Keywords: Dynamic Stretching, Static stretching, Warm-up, Dynamic balance, Static balance